Community Service Through the Practice of Daily Prayers in Learning Activities for Early Childhood at SDN 4 Kedokan Agung - Linda Nurazizah (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2023)
Writing this community  service  carticle amis to implove childern’s ability to pray and find out how well childern are accustomed to appliying daily prayers at SDN 4 Kedokan Agung. The method of writing this community  service article uses pretest-postest, and applies the rote method to children, as well as delivering material about daily prayers, teaching good habbits to children starting from how the pray. Spiritual value is a very important value to be applied to every human being to mantain balance in activies and worship. The application of spiritual values must also be instilled from an early age, aspecially to childern. Though the application of habituation method of daily prayers in learning activies, it is able to improve childern’s ability to pray. Teaching children to pray in every activity can also train discipline, patience and always remember Allah both in starting activities. Appliying habituation so that children are accustomed to praying in every activity is very important because it is the basis for children to behave so that They have a strong personality and commendable morals. Therefore, the habituation method in learning activities is very aeffective in training and improving children’s ability to pray.